A Dynamic Fitting Room Based on Microsoft Kinect and Augmented Reality Technologies - Chang, Hsien-Tsung; Li, Yu-Wen; Chen, Huan-Ting; Feng, Shih-Yi; Chien, Tsung-Tien (Human-Computer Interaction. Interaction Modalities and Techniques, 2013)
In recent years, more and more researchers try to make Microsoft Kinect and Augmented Reality (AR) into real lives. In this paper, we try to utilize both Kinect and AR to build a dynamic fitting room. We can automatically measure the clothes size of a user in popular brands or different country standards. A user can utilize gesture to select cloths for fitting. Our proposed system will project the video dynamically of dressing selected clothes in accordance with the captured video from Kinect. This system can be utilized in clothing store, e-commerce of clothes shopping, and at your home when you are confusing choosing a clothes to wear. This can greatly reduce the time you fitting clothes.